Komatiitic explosive volcanism and its tectonic setting in Finland, the Fennoscandian (Baltic) Shield - M. Saverikko (Bulletin of the Geological Society of Finland, 1990)
The variously explosive komatiitic volcanism in Finland was virtually confined to the Archaean continental segment, where it occurred in the Lapland and Kuhmo‒ Suomussalmi greenstone belts between 3.0 Ga and 2.5 Ga, in the continental borderland at 1.97 Ga, and in the continental shelf break 1.91‒1.88 Ga ago. The Archaean continent comprised the Saamian craton, which stabilized at 3.1‒3.0 Ga before splitting into an array of sialic megablocks. Except for the NW-trending rifts, the linear crustal openings of the Fennoscandian greenstone belts constituted a radial swarm of aulacogens caused by domal uplift in connection with shield-wide mantle upwelling. Diapirism resulted in the Lapponian pyroclastic komatiite zone of mantle-activated rifting and in the large Solovetski mantle plume in the USSR, along which continental breakup reached no more than an embryonic stage of divergence. The Finnish greenstone belts underwent three periods of supracrustal evolution from cratonic deposition and/or continental rifting to oceanic or mantle-activated rifting. The extensional stage of the greenstone-belt genesis is recognizable in Lapland but not in the Kuhmo‒Suomussalmi area, in the ductile? periphery of the continental plate, where sagduction obscured the geological history. In Lapland, the komatiitic central-vents opened at rift‒aulacogen intersections. Some signs of volcanic bursting, albeit obscure, can be traced in the earlier ultramafics, namely in the initial komatiitic greenstones beneath the cratonic metasediments and in those associated with bimodal metavolcanics. Pyroclastics formed in all the komatiitic rock types but the pyroxene peridotitic komatiite (MgO 18‒30 wt%, anhydrous basis) was the predominant substance to extrude in enormous magmatic explosions during the terminal stage of mantle upwelling. After the Karelian anorogenic period, mantle activity produced two ophiolitic suites from the mantle plumes 1.97‒1.96 Ga ago. The one at Outokumpu brought about volcaniclastic komatiites under shallow-water to ...